Práticas de gestão em escolas públicas estaduais de Porto Alegre: um pacto de equipes - Reichert, Andreana Catarina Haas (Universidade do Vale do Rio dos Sinos, 2015)
This Dissertation discusses what knowledge, skills, attitudes of school administrators qualify democratic school management. Therefore, this study aimed to analyze the public school management, targeting to identify the capacities that qualify the practices of the management team. The study was conducted over the experience in school management in private schools of Porto Alegre (RS) municipality, in order to identify, through dialogue with eleven State level public school managers, their experiences with the democratic public administration. Thus, we obtained evidence that, for the management competence, we must invest in the continuing education of managers in the areas that address specific knowledge of school management. Based on Demo (2012), Ferreira (2007), Libâneo (2013), Lück (2000), Paro (2012), among others, it is proposed, besides the need of professionalization, the role of manager with skills, attitudes and abilities. It was found that the stakeholders surveyed desire the domain of the expertise of democratic school management, realizing that there is a need of domain of knowledge for able management and not only their practical experience, their theoretical framework or their idiosyncrasies.
Keywords: Gestão democrática; Educação básica; Competências gestoras; Democratic management; Basic education; Management skills; ACCNPQ::Ciências Humanas::Educação